UNIVERSITY PROFESSORS: A VIEW FROM GENERAL SELF-EFFICACY AND WORK ENGAGEMENT - Lozano-Paz, Carmen Rosa (2017)
This research aims at understanding general self-efficacy and work engagement of professors of the Psychology Program of a private university in metropolitan Lima. To reach this objective, in-depth interviews with seven professors were conducted: three of them were women and four were men. Based on those interviews, it was possible to understand what personal factors have helped said professors to carry out their work as well as with what they are engaged. Finally, it was concluded that professors have self-efficacy, as they assess their skills and their environment to achieve their goals. Another finding was that they are engaged with their teaching work, and this is based on their interaction with their students, since they do more research and are up-to-date with current practices in their field.